Service quality of mortgage real estate, consumer loan intention, buying behavior of luxury apartments, personal credit at Vietnamese commercial banks - Doan, Thi Diep Uyen; Nguyen, Duy Nhien; Nguyen, Thi Thu Hoai; Nguyen, Thuy Linh; Nguyen, Thi Thai Thuy; Tran, Thi Kim Phuong (CENTRAL ASIA AND THE CAUCASUS, 2021)
In the context of deepening international economic integration, the level of competition between Vietnamese commercial banks is becoming more and more fierce, the service quality factor plays an increasingly important role in the success of the banking industry. existence and development of commercial banks. The article analyzes the factors affecting the quality of mortgage real estate valuation services and the influence of the quality of mortgage real estate valuation services on consumer loan intention and buying behavior of luxury apartments. in Vietnamese commercial banks. The study was conducted in 3 major cities of Vietnam, Hanoi, Ho Chi Minh and Da Nang, these 3 cities represent the 3 regions of the country: The North, the Central and the South. The research results show that there are 5 factors that affect the quality of mortgage real estate valuation services, including: Reliability; Responsiveness; Guarantees; Sympathy; Professional qualifications of appraisal staff... In which, the factor with the highest level of impact is assurance. In addition, the quality of mortgage real estate valuation services, consumer loan intentions, apartment/land location; design and function of the apartment; The reputation and quality of investors and a new factor in this study compared with previous studies is that the spiritual factor has a positive and statistically significant impact on the buying behavior of high-end apartments. citizen. Finally, the interest rate variable has a statistically significant moderating role in the relationship between consumer borrowing intentions and people's buying behavior of luxury apartments.